Improving Students' Critical Thinking Ability Through Guided Inquiry Model with Scientific Approach on Ecosystem Material - Komala, Ratna; Azrai, Eka Putri; Handayani, Mira Wisda (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to determine the effect of a guided inquiry learning model with a scientific approach on students' critical thinking skills on ecosystem material. The research was conducted in the even semester of the 2023/2024 academic year at one of the high schools in Jakarta, Indonesia. The research method used was a quasi-experiment with Nonequivalent Control Group Design. The research sample used was 52 students, with each class totaling 26 students using a simple random sampling technique. Based on the study's results, the experimental class's average value was 87.27, and the control class was 80.15. The t-independent test results show that the guided inquiry learning model, with a scientific approach, affects students' critical thinking skills on ecosystem material. Applying a scientific approach to the guided inquiry learning model can allow teachers to train and improve students' critical thinking skills. This learning model and approach encourages active participation, stimulates curiosity, and helps students gain a deeper understanding.